Monitoring Serum Creatinine, Blood Urea Nitrogen in Patients Brain Injury with Mannitol Therapy - Sari, Erni A; Suharjono, Suharjono; Wahyuhadi, Joni (Folia Medica Indonesiana, 2020)
Increased intracranial pressure is a further effect of brain injury due to structural damage and osmotic and water imbalances (Edema). Mannitol works in the proximal tubules and mannitol in the absorption of tubular cells by the mechanism of pinocytosis. The fluid transfer will draw fluid into the intracellular, so that the cell will be switched and broke. This phenomenon is referred to as the phenomenon of